Tropical forest conversion to rubber plantation in southwest China results in lower fungal beta diversity and reduced network complexity. Issue 7 (18th June 2019) - Song, Hokyung; Singh, Dharmesh; Tomlinson, Kyle W; Yang, Xiaodong; Ogwu, Matthew Chidozie; Slik, J W Ferry; Adams, Jonathan M
ABSTRACT: Despite the extensive, ongoing conversion of tropical forests to rubber plantation, the effects of this land-use change on soil fungal community diversity and composition are still poorly known. We compared a network of sites of tropical forest in southern Yunnan, China, with a network of rubber plantation sites originally derived from this forest. Soil DNA was amplified for ITS2 and sequenced using Illumina MiSeq. We found that there was a major shift in community composition across all phyla, including a large reduction in ectomycorrhizal fungi likely related to the absence of hosts. Conversion from forest to rubber plantation had no effect on total fungal α-diversity, but rubber plantation had lower β-diversity, resulting in lower overall gamma diversity. Networks based on co-occurrence of operational taxonomic unit in each land-use type showed that network complexity decreased with land-use change from forest to rubber plantation. Further investigation of soil functionality is needed to investigate whether this lower network complexity is related to reduced soil ecosystem resilience. Abstract : We compared soil fungal diversity of tropical forest fragments and rubber plantations in China, finding greater beta diversity in the forest habitat.